Evaluation of safety and efficacy of inhaled ambroxol in hospitalized adult patients with mucopurulent sputum and expectoration difficulty - Zheng, Zeguang; Yang, Kai; Liu, Ni; Fu, Xiuhua; He, Huijie; Chen, Hong; Xu, Peijun; Wang, Jing; Liu, Maofeng; Tang, Yuling; Zhao, Fengzi; Xu, Shufeng; et al. (Frontiers in Medicine, 2023)
Background: Ambroxol is a widely used mucoactive drug in sputum clearance of respiratory diseases by oral and injection. However, there is paucity of evidence for inhaled ambroxol in sputum clearance. Methods: This study performed a multicenter, randomized, double-blind, placebo-controlled, phase 3 trial at 19 centers in China. Hospitalized adult patients with mucopurulent sputum and expectoration difficulty were recruited. Patients were randomized 1:1 to receive inhalation of either ambroxol hydrochloride solution 3 ml (22.5mg) + 0.9% sodium chloride 3 ml or 0.9% sodium chloride 6ml twice daily for five days, with an interval of more than six hours. The primary efficacy endpoint was the absolute change in sputum property score after treatment compared to baseline in the intention-to-treat population. Results: Between Apr 10, 2018 and Nov 23, 2020, 316 patients were recruited and assessed for eligibility, of whom 138 received inhaled ambroxol and 134 received placebo were included. Patients who received inhaled ambroxol had a significantly greater decrease in sputum property score compared with patients who received inhalation of placebo (difference: -0.29; 95% CI: -0.53 to -0.05; P = 0.0215). Compared with placebo, inhaled ambroxol also significantly reduced more expectoration volume in 24 h (difference: -0.18; 95% CI: -0.34 to -0.03; P: 0.0166). There was no significant difference in the proportion of adverse events between two groups, and no deaths were reported. Discussion: In hospitalized adult patients with mucopurulent sputum and expectoration difficulty, inhaled ambroxol was safe and effective for sputum clearance compared with placebo.